Recent Advances in CXCL12/CXCR4 Antagonists and Nano-Based Drug Delivery Systems for Cancer Therapy - Ruogang Zhao; Jianhao Liu; Zhaohuan Li; Wenhui Zhang; Feng Wang; Bo Zhang (MDPI AG, 2022)
Chemokines can induce chemotactic cell migration by interacting with G protein-coupled receptors to play a significant regulatory role in the development of cancer. CXC chemokine-12 (CXCL12) can specifically bind to CXC chemokine receptor 4 (CXCR4) and is closely associated with the progression of cancer via multiple signaling pathways. Over recent years, many CXCR4 antagonists have been tested in clinical trials; however, Plerixafor (AMD3100) is the only drug that has been approved for marketing thus far. In this review, we first summarize the mechanisms that mediate the physiological effects of the CXCL12/CXCR4 axis. Then, we describe the use of CXCL12/CXCR4 antagonists. Finally, we discuss the use of nano-based drug delivery systems that exert action on the CXCL12/CXCR4 biological axis.